ANALISA PENGARUH PENGGUNAAN MATERIAL KOMPOSIT PADA INTAKE MANIFOLD TERHADAP KONSUMSI BAHAN BAKAR PADA SEPEDA MOTOR - Nurohim, Aris; Kadir, Abd; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The purpose of this study was to determine the fuel consumption of the motorcycle Yamaha Vega ZR assembled in 2009 by using the intake manifold with the basic material of the fiber composites. This studyused an experimental method. The sample is a Yamaha Vega ZR motorcycle is assembled in 2009 to number Engines: 5D9-191066. Data collected through the experimental method. The consumption of fuel measuredin static conditions with a measuring glass. Testing is done by measuring the time required by the machine to spend in a given volume of fuel at the 1500 rpm ,2500 rpm and 4000 rpm. Results showed that the differencein the time required to spend 10 ml of fuel between the use of intake manifold standard with intake manifold fiber composite fibers in the round 1500 rpm is 0.11 minute, the lap 2500 rpm is 0.08 minute and at enginespeed of 4000 rpm is 0.04 minute. The difference in the average time required to spend 10 ml of fuel is 0.07 minute at 1500 rpm until the engine rotation 4000 rpm. Thus, fuel consumption decreases when using theintake manifold with the basic material of the palm fiber composite intake manifold using standard.Keywords: palm fiber composites, intake manifold and fuel consumption.